Decoration of carbon dots over hydrogen peroxide treated graphitic carbon nitride: Exceptional photocatalytic performance in removal of different contaminants under visible light - Asadzadeh-Khaneghah, Soheila; Habibi-Yangjeh, Aziz; Nakata, Kazuya (Journal of Photochemistry and Photobiology A: Chemistry, 2019)
[Display omitted] •Exceptional photocatalyst is reported by combining activated g-C3N4 with carbon dots.•Activity of the nanocomposite in degradation of RhB is 34.7 times superior than g-C3N4.•The nanocomposite completely degraded RhB in 60 min under visible-light irradiation.•The nanocomposite displayed exceptional activity in removal of MB, fuchsine, and Cr (VI). The development of novel photocatalysts with considerable activity for completely removal of different pollutants from the environment is a dominating goal of modern chemistry. In this study, carbon dots (CDs) were adhered to the graphitic carbon nitride activated by hydrogen peroxide (ag-C3N4) to fabricate photocatalysts with exceptional ability upon visible-light illumination. Interestingly, the BET surface area, visible-light absorption characteristics, and electron-hole separation yield of the pristine g-C3N4 were improved after activation with H2O2 and decoration of CDs. The binary nanocomposite was used for degradation of MB, RhB, fuchsine, and phenol and photoreduction of Cr(VI) under visible light. The nanocomposite exhibited excellent photocatalytic performance with 100% removal of RhB in 60 min, which is almost 34.7 folds as premier as the pristine g-C3N4. Reactive species scavenging measurements displayed that O2−, OH, and h+ had significant roles for photodegradation of RhB. The possible mechanism was proposed regarding how activation with H2O2 and decoration of CDs improved the photocatalytic performance of g-C3N4. Also, stability of the composite was characterized through cyclic photocatalytic tests.